Flood Preparedness in United Kingdom and China: A Comparison Study Focusing on Social and Economic Factors - Ruishan Gong; Naif R Alrehaili (International Journal of Disaster Management, 2022)
The paper aims to explore the social and economic factors influencing the flood preparedness of Zhengzhou, China and Leeds, United Kingdom residents. As one of the chosen areas, Zhengzhou experienced a terrible flood with an inaccurate weather forecast and little pre-flood preparedness in July 2021. On the other hand, Leeds has a long history of frequent floods. Wetter winters and stormy weather caused by climate change led to increased floods in Leeds. The consistent seasonal floods keep damaging residents and their properties, leading to economic losses. The authors conducted semi-structured interviews with residents who experienced floods in Zhengzhou and Leeds. Comparative parameters included economic and social, as these factors are hugely different in the study areas. The results showed that factors like education influence the households’ flood preparedness; likewise, economic factors like disposable income also affect the willingness of residents to spend on flood preparedness. Furthermore, the results revealed that with proactive flood management, both communities progressed in minimising the post-adverse effects of floods.